2019
DOI: 10.1021/acs.jcim.9b00304
|View full text |Cite
|
Sign up to set email alerts
|

Intuition-Enabled Machine Learning Beats the Competition When Joint Human-Robot Teams Perform Inorganic Chemical Experiments

Abstract: Traditionally, chemists have relied on years of training and accumulated experience in order to discover new molecules. But the space of possible molecules is so vast that only a limited exploration with the traditional methods can be ever possible. This means that many opportunities for the discovery of interesting phenomena have been missed, and in addition, the inherent variability of these phenomena can make them difficult to control and understand. The current state-of-the-art is moving toward the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
0
34
0
2
Order By: Relevance
“…[296] ¾hnliche Closed-Loop-Optimierungen werden auch für Materialanwendungen durchgeführt. Tr otz unterschiedlicher Analytik fürd ie verschiedenen interessierenden Eigenschaften ist der Gesamtablauf derselbe.O ptimierungsziele waren hier unter anderem die Emissionsintensitätv on Quantenpunkten, [297] die Umwandlung und Partikelgrçße bei einer Copolymerisation, [290] die Identifizierung von Kristallisationsbedingungen fürP olyoxometallate, [298,299] die Herstellung von Bose-Einstein-Kondensaten [300] und die Synthese einer Metall-organischen Gerüstverbindung (MOF) mit großer Oberfläche. [301] Besonders bemerkenswert ist die Optimie-…”
Section: Methodsunclassified
See 1 more Smart Citation
“…[296] ¾hnliche Closed-Loop-Optimierungen werden auch für Materialanwendungen durchgeführt. Tr otz unterschiedlicher Analytik fürd ie verschiedenen interessierenden Eigenschaften ist der Gesamtablauf derselbe.O ptimierungsziele waren hier unter anderem die Emissionsintensitätv on Quantenpunkten, [297] die Umwandlung und Partikelgrçße bei einer Copolymerisation, [290] die Identifizierung von Kristallisationsbedingungen fürP olyoxometallate, [298,299] die Herstellung von Bose-Einstein-Kondensaten [300] und die Synthese einer Metall-organischen Gerüstverbindung (MOF) mit großer Oberfläche. [301] Besonders bemerkenswert ist die Optimie-…”
Section: Methodsunclassified
“…Trotz unterschiedlicher Analytik für die verschiedenen interessierenden Eigenschaften ist der Gesamtablauf derselbe. Optimierungsziele waren hier unter anderem die Emissionsintensität von Quantenpunkten, [297] die Umwandlung und Partikelgröße bei einer Copolymerisation, [290] die Identifizierung von Kristallisationsbedingungen für Polyoxometallate, [298, 299] die Herstellung von Bose‐Einstein‐Kondensaten [300] und die Synthese einer Metall‐organischen Gerüstverbindung (MOF) mit großer Oberfläche [301] . Besonders bemerkenswert ist die Optimierung der MOF‐Synthese von Moosavi et al., da hier die relative Bedeutung der Syntheseparameter aus Daten aus früheren MOF‐Synthesen abgeschätzt wurde, um maximal unterschiedliche experimentelle Startdesigns zu ermöglichen, wodurch direkt mit der empirischen iterativen Optimierung begonnen werden konnte [301] …”
Section: Beispiele Für (Teil)autonome Entdeckungenunclassified
“…[292,293] Multi-step reactions are particularly challenging to optimize because the effects of changing one parameter can propagate through downstream process steps.T hey are typically broken up into individual synthetic steps to improve the tractability of the problem [294,295] or optimized approximately through screening, rather than through true closed-loop feedback. [296] Similar closed-loop optimizations have been demonstrated for materials-focused applications.D ifferent properties of interest necessitate different analytical endpoints,b ut the overall workflow is the same.O ptimization goals have included the emission intensity of quantum dots, [297] the conversion and particle size resulting from ac opolymerization, [290] the identification of crystallization conditions for polyoxometalates, [298,299] the production of Bose-Einstein condensates, [300] and the realization of ametal-organic framework (MOF) with high surface area. [301] TheM OF synthesis optimization by Moosavi et al is particularly noteworthy in that prior data on syntheses of other MOFs were used to estimate the relative importance of synthetic parameters to enable am aximally diverse initial design of experiments, jump-starting the phase of iterative empirical optimization.…”
Section: Iterative Discovery Of Chemical Processes 441 Discovery Omentioning
confidence: 99%
“…Different properties of interest necessitate different analytical endpoints, but the overall workflow is the same. Optimization goals have included the emission intensity of quantum dots, [297] the conversion and particle size resulting from a copolymerization, [290] the identification of crystallization conditions for polyoxometalates, [298, 299] the production of Bose–Einstein condensates, [300] and the realization of a metal–organic framework (MOF) with high surface area [301] . The MOF synthesis optimization by Moosavi et al.…”
Section: Examples Of (Partially) Autonomous Discoverymentioning
confidence: 99%
“…In addition, the algorithm explored a wider range of space that would need to be performed either by human or purely random search. Recently, the same researchers observed that collaboration between smart robotics and humans may be even more efficient than either alone [22]. Grizou and colleagues described a chemical robotic discovery assistant equipped with a curiosity algorithm that can efficiently explore a complex chemical system in search of complex emergent phenomena exhibited by proto-cell droplets [23].…”
Section: Machine Learning Towards Chemical Space Explorationmentioning
confidence: 99%